Education on the Hazard of Cigarette Smoke on Toddlers' Health as an Effort to Improve Community Knowledge - Emi Sutrisminah; Khusnu Ummil Umroh; Kiki Hartati; Okky Liya Rohmah Safitri (Jurnal Abmas Negeri (JAGRI), 2026)
Exposure to cigarette smoke is a serious risk factor for the health of toddlers as passive smokers. The high level of cigarette consumption and the low level of public awareness regarding the impact of cigarette smoke on toddlers remain significant family health problems. This Community Service activity was conducted on January 17, 2026, in RT 02/RW 06, Sembungharjo Village, Genuk District, Semarang City, with the aim of improving community knowledge about the hazards of cigarette smoke on toddlers’ health. The methods used included pre-test and post-test questionnaires, educational counseling, and interactive discussions supported by leaflet media. A total of 30 participants were involved in the activity. Evaluation was carried out through analysis of questionnaire results and participants’ activeness during the session. The results showed a significant increase in subjects’ knowledge (p < 0.05). This activity contributed to enhancing community awareness in protecting toddlers from exposure to cigarette smoke.